Association between changes of frailty status/frailty components status and rapid loss of kidney function in middle- aged and older populations - Deng, Ying; Lai, JiaHui; Tang, LeiLe; Li, ShaoMin; Guo, XingHua; Kang, JianHao; Liu, Xun (BMC Nephrology, 2024)
Frailty and its components are proposed to associate with kidney function, but little attention is paid to the significance of changes in their status on rapid loss of kidney function. This study aimed to investigate the association between changes in frailty and its components status with rapid loss of renal function.